IT-driven business models : global case studies in transformation - Kagermann, Henning (John Wiley and Sons Ltd, 2011)
"This book will show organizations how business model innovation should be a key focus area in today's global economy. It features cases from businesses around the globe who have developed their own business models to acheive high levels of per